Physician Perspectives on the Optimization of Carbapenem Use in a Four Hospital, Large Urban Healthcare System. (4th October 2017) - Frew, Paula; Fenimore, Vincent; Jacob, Jesse T; Sherman, Amy; Bedoya, Federico Palacio; Goolsby, Tiffany; Pack, Jan; Johnson-Martinez, Krysta; Wong, Jordan; Sexton, Mary Elizabeth; Kandiah, Sheetal; Fridkin, Scott; et al.
Abstract: Background: Carbapenem resistance is an emerging public health threat, but provider-level drivers for carbapenem use are not well understood. We aimed to explore prescribing physician attitudes, beliefs, and knowledge to provide evidence on carbapenem use current practices. Methods: We conducted in-depth interviews with physicians representing different specialties and experience levels at 4 urban hospitals in Atlanta using a semi-structured interview guide developed by a team of clinicians and experts in qualitative research and implementation science. We performed team-based qualitative analyses inclusive of codebook development, iterative coding, and interrater reliability assessment. Pearson correlation tests were used to evaluate patterns and relationships based on R≥0.80 to determine themes. Results: Among 35 physicians, most were men (57%) and attending physicians (51% in practice for 1–10 years; 14% >10 years); 34% were house staff, and they represented 10 practice areas including hospital medicine (28%), critical care (22%), and surgery/surgical specialties (13%). Four major themes emerged: 1) a broad variation in general concern (e.g., lowest in surgery and highest in hospital medicine) about antibiotic resistance across specialties and provider levels; 2) patient management challenges attributed to initial emergency department (ED)/outside facilities' prescribing practices; 3) more frequent carbapenem use reported by trauma surgeons and oncologists (compared with other specialties) and 4) concern that information sources (e.g., Up-to-Date, Epocrates®, hospital antibiograms) for aiding in antibiotic choice decision-making were limited, scattered, and not perceived as tailored to specialty. Conclusion: The findings reflect differences in perceived attitudes, value, and norms toward carbapenem use across practice areas and identify areas to target interventions, in particular antibiotic starts in the ED. Although there is strong support for antibiotic stewardship policies and practices, providers desire approaches targeted to their specialty and tailored to address relevant issues. Disclosures: S. Fridkin, Pfizer: Consultant and Grant Investigator, Consulting fee and Research support